APPLYING INTERNATIONAL HUMANITARIAN LAW PRINCIPLES IN THE CYBER WARFARE CONTEXT (INDONESIAN PERSPECTIVES) - Anang Setiyawan (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
State military strategy and weaponry may reflect the economic, political and describes the mastery and the capability of technology. Technologies turn the conventional war paradigm that is kinetic and located in physics domain towards modern warfare using non kinetic weapon and located in fifth domain, namely cyberspace. This war techniques and methods is emphasized to attack through computer network with particular political intent or national security of a state with the aim of causing damage, chaos, death, undermine and disrupt the defense system, transportation system, telecommunication system, banking system and other state’s vital assets systematically without crossing the state boundaries.In the conventional warfare is relatively easy to implement the International Humanitarian Law Principle but there are some constraints in the implementation these principles in cyber warfare, such as the nature of anonymity, military and civilian infrastructures network interconnection, lack of international and national regulation on cyber warfare/cyber attack so that countries unilaterally interpret the rules of war in the cyber domain. These problems led to much debate over whether cyber warfare are in the scope of IHL or not due to non-kinetic cyber attack therefore it cannot be considered as an armed conflict in the truest sense. This determination is very important because it is associated with the implementation of the basic provisions of IHL during armed conflict, such as the protection to the non-combatant, civilian, and civilian objects, etc.Several developed countries stated cyberspace as their new warfare domain and has been developing cyber units to equip their military forces both to conduct cyber and defend against cyber attack in cyberspace. Eugene Kaspersky stated that global cyber war will be more dangerous and increasing. The attacks carried out will be more systematic and sophisticated than before. Indonesia with 82 million Internet users should pay more attention to this issue because in last three year Ministry of ICT state that 3,9 Millions cyber attacks against Indonesia's domain. we can imagine if this attack carried out on vital infrastructure such as mass transportation, banking systems, defense systems, air traffic control systems, or civil nuclear power plants will not only cause malfunctions, but has the potential to cause physical damage, injury even civilian death.Therefore, in 2013 the Indonesian government began to develop a cyber defense system to counter cyber attacks that could interfere with the sovereignty, defense and national interests of Indonesia. Director General of the Indonesian Ministry of Defense said that regulatory and presence of cyber command center are important factors that must be considered in order to run well. Based on the above description, the authors are interested in developing the rules concept of cyber warfare based on IHL principles and integrate with military force in order to maintain the sovereignty of Indonesia in the real and cyber domains.Keywords: cyberwar, international humanitarian law, Indonesia, policy, strategy